Self-Efficacy as a Mediation the Influence of Proactive Personality on Career Adaptability in Early Adults - Afero, Fanny Irawan; Dimala, Cempaka Putrie; Ibad, M Choirul (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2023)
Early adulthood, as defined by Huclock (2012), is a transitional period from adolescence to adulthood, spanning the age range of 18 to 40 years. The fact that 80% of Indonesian students do not work in fields related to their college majors indicates a discrepancy between graduates' qualifications and the job demands in the labor market. Furthermore, data stating that only about 27% of graduates have jobs in their field of study highlights a high level of incongruity between graduates' qualifications and the job demands in specific industries or sectors. This research aims to explore the role of self-efficacy as a mediator of the influence of proactive personality on career adaptability among young adults in Kabupaten Karawang. The distribution of questionnaire data is conducted electronically. The instruments used in this study include the Career Adapt-Abilities Scale (CAAS), The General Self-Efficacy Scale (GSES-12), and the Proactive Personality Scale (PPS), all of which have been translated into Indonesia. The results of the analysis indicate that proactive personality significantly influences career adaptability. However, self-efficacy does not have a significant influence on career adaptability. Neither proactive personality nor self-efficacy individually has an impact on career adaptability. Data analysis using mediation analysis shows that there is no mediating role of self-efficacy between proactive personality and career adaptability among young adults in Kabupaten Karawang.Dewasa awal, menurut Huclock (2012), adalah periode peralihan dari masa remaja menuju dewasa dengan rentang usia 18 hingga 40 tahun. Fakta bahwa 80% mahasiswa Indonesia tidak bekerja sesuai dengan jurusan kuliahnya menunjukkan adanya kesenjangan antara kualifikasi yang dimiliki oleh lulusan dengan kebutuhan dan permintaan pekerjaan di pasar kerja. Selain itu, data yang menyatakan hanya sekitar 27% lulusan yang memiliki pekerjaan sesuai dengan bidang ilmunya menunjukkan tingginya tingkat ketidaksesuaian antara kualifikasi lulusan dengan tuntutan pekerjaan di industri atau sektor tertentu. Penelitian ini bertujuan untuk mengeksplorasi peran efikasi diri sebagai perantara dari pengaruh kepribadian proaktif terhadap adaptabilitas karir pada dewasa awal di Kabupaten Karawang. Penyebaran data kuesioner melalui media elektronik. Instrumen yang digunakan dalam penelitian ini mencakup Skala Adaptabilitas Karir (CAAS), Skala Efikasi Diri Umum (GSES-12), dan Skala Kepribadian Proaktif (PPS), yang semuanya telah diterjemahkan ke dalam Bahasa Indonesia. Hasil analisis menunjukkan bahwa kepribadian proaktif memiliki pengaruh signifikan terhadap adaptabilitas karir. Namun, efikasi diri tidak memiliki pengaruh signifikan terhadap adaptabilitas karir. Baik kepribadian proaktif maupun efikasi diri secara individual tidak memiliki pengaruh pada adaptabilitas karir. Analisis data menggunakan analisis mediasi menunjukkan bahwa tidak ditemukan peran mediasi dari efikasi diri antara kepribadian proaktif dan adaptabilitas karir pada dewasa awal di Kabupaten Karawang.